Argentina in the global Middle East - Balloffet, Lily Pearl (Stanford University Press, 2020)
"Argentina in the Global Middle East connects modern Latin American and Middle Eastern history through their shared links to global migration systems. In this study of Argentina's Arab diaspora, and its many intersections with other sectors of Argentine society, Lily Balloffet brings a migratory lens to Argentine history from the late-nineteenth to the twenty-first century"--